Case report: Concurrent MOG antibody-associated disease and latent infections in two patients - Kulsvehagen, Laila; Woelfle, Tim; Ayroza Galvão Ribeiro Gomes, Ana Beatriz; Lipps, Patrick; Neziraj, Tradite; Flammer, Julia; Leuzinger, Karoline; Derfuss, Tobias; Kuhle, Jens; Papadopoulou, Athina; Pröbstel, Anne-Katrin (Frontiers in Immunology, 2024)
Objectives Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) is frequently preceded by infections. The underlying pathomechanism, however, remains poorly understood. Here, we present the clinical data of two MOGAD patients with concurrent syphilis infection and investigate the reactivity of patient-derived antibodies to MOG and Treponema pallidum (T. pallidum). Methods Longitudinal serum samples and soluble immunoglobulins in single B cell supernatants were measured for MOG reactivity by a live cell-based assay. Reactivity against T. pallidum was assessed by enzyme-linked immunosorbent assay. Results The two patients presented MOGAD and concurrent latent syphilis infection, manifesting as cervical myelitis and unilateral optic neuritis, respectively. The first patient had been living with HIV on antiretroviral therapy, and the second was concomitantly diagnosed with chronic hepatitis B infection. Upon screening of B cell supernatants, we identified reactivity to MOG or T. pallidum. Notably, one B cell showed reactivity to both antigens. Discussion The coexistence of MOGAD diagnoses and latent syphilis, alongside the identification of antibody reactivity to MOG and T. pallidum, underscores the potential pathomechanistic link between syphilis infection and subsequent autoimmune neuroinflammation. Cross-reactivity between MOG and T. pallidum antibodies remains to be validated on a molecular level, and further characterization of infectious triggers associated with MOGAD is needed.